IMPACT OF ISLAMIC ACCOUNTING PRACTICES ON WORKERS MORAL BEHAVIOR IN BANKS OF PESHAWAR - Khan, Waseem Ullah; Hashim, Muhammad; Bhatti, Anam; Ullah, Habib (International Journal of Psychosocial Rehabilitation, 2020)
Business operations have been reported various financial frauds and embezzlement and need to be traced and reviewed with ethical and moral based accounting system to minimize misappropriation of financial data. Islamic accounting practices enriched with ethical standard and moral education with based purely on Islamic way of life and law. The system can be considered a tool to reduce monetary frauds and shaped the individual psyche to prevent them in future. The dimensions of Islamic accounting system (stewardship and accountability) were considered the important predictors of workers moral behavior towards moral responsibility. The study was conducted in commercial banks situated in Peshawar. The data was obtained through survey. Seven major banks were selected as sample size for this study. Information obtained with the help of 70 filled questionnaires. The results showed a strong relation between Islamic way of accounting and worker moral psyche and behavior. The study will contribute in the field of Islamic accounting literature and will provide a new insight for financial managers. Recommendations are given in the last.